PENILAIAN BAHAN AJAR MODUL MENJAHIT SAKU PADA MATA KULIAH TEKNIK JAHIT - Adiharsanti, Rahmi; R. Lubis, Harsuyanti; Nawimar, Wesnina (Practice of Fashion and Textile Education Journal, 2022)
This research aims to assess teaching materials in the form of modules with pocket sewing techniques. This research was conducted to experts panelists with related fields of expertise and carried out in the odd semester of 2021/2022 academic year. Pre-Expermental Method is used in this research with One-Shot Case Study model. Descriptive quantitative technique used as data analysis technique in this reasearch. Using a single variable namely the assessment of teaching materials pocket sewing module. The reasearch indicators used based on good module characteristic (Self Instructional, Self Contained, Stand Alone, Adaptive, and User Friendly) and presentation quality elements (Consistensy, Form, Organization, Attractiveness, Font Shape and Size, and Spacing). Data collected through open-close questionnaire with rating scale. Results of this research stated that assesment based on good module characteristic get 79,58% and assestment based on presentation quality elements gets 90,04%. Assesment based on good module characteristic Self Instructional indicators gets percentage of 85,55%, Adaptive 80%, Self Contained 75%, Stand Alone 75%, and User Friendly 74,71%. And assesment based on presentation quality elements Organization indicator gets 94,28%, Consistensy with 90%, Font Shape and Size 90%, Spacing 90%, Form 86,66% and 85% Attractiveness. So the results of the pocket sewing module assessment get a good score and can be used as an alternative teaching material in the technical sewing course.